Modulating Antibody Functionality in Infectious Disease and Vaccination. Issue 11 (November 2016) - Gunn, Bronwyn M.; Alter, Galit
Abstract : Induction of pathogen-specific binding antibodies has long been considered a signature of protective immunity following vaccination and infection. The humoral immune response is a complex network of antibodies that target different specificities and drive different functions, collectively acting to limit and clear infection either directly, via pathogen neutralization, or indirectly, via pathogen clearance by the innate immune system. Emerging data suggest that not all antibody responses are equal, and qualitative features of antibodies may be key to defining protective immune profiles. Here, we review the most recent advances in our understanding of protective functional antibody responses in natural infection, vaccination, and monoclonal antibody therapeutics. Moreover, we highlight opportunities to augment or modulate antibody-mediated protection through enhancement of antibody functionality. Trends: An antibody Fc domain interacts with innate immune cells, mediating a range of functions, including effector mechanisms, to limit and clear infection. Fc-mediated antibody functionality is increasingly being recognized as a critical aspect of humoral immunity against infectious diseases. Antibody functionality is modulated during disease and vaccination through both subclass selection and glycosylation of the antibody Fc domain. Broadly neutralizing monoclonal antibodies against HIV-1 and influenza viruses require Fc-mediated functionality to confer immune protection. Comprehensive profiling of the humoral response beyond titer and neutralization can identify underlying protective signatures of antibody-mediated protection. Different vaccines, adjuvants, regimens, and vectors induce distinct antibody functional profiles, and future vaccines may be designed to direct antibody functionality.